FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PROGRAM PENGELOLAAN PENYAKIT KRONIS (PROLANIS) PADA PASIEN DIABETES MELITUS DI PUSKESMAS CIANJUR KOTA KABUPATEN CIANJUR - Ricko Dwi Haryanto; Ditte Ayu Suntara (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Abstract : Chronic Disease Management (Prolanis) for type 2 diabetes treatment is a health service delivery system with a proactive approach. Prolanis is implemented to improve the quality of life of patients with chronic diseases, with 75% of participants registered at FKTP achieving 'good' results in type 2 diabetes tests, according to clinical guidelines to prevent complications. The aim of this study is to identify factors related to the use of Prolanis among Diabetes Mellitus patients at Cianjur City Health Center, Cianjur Regency. This is a quantitative study using a cross-sectional method. The study population consists of 77 Diabetes Mellitus patients. The sampling method is non-probability using purposive sampling techniques. The results of this study show that most respondents fall into the low Prolanis utilization category, and most respondents are female, highly educated, and unemployed. They have good knowledge and receive High support from family and healthcare workers. Most respondents have good pain perception and need perception. There is also a significant relationship between the variables of knowledge, family support, healthcare worker support, pain perception, need perception, and the use of Prolanis in the working area of Cianjur City Health Center, Cianjur Regency.Keywords: Prolanis, type 2 diabetes, use of Prolanis, patients, quantitative research..